A Finite Difference Method for Smooth Solution of a System of Linear Volterra Integral Equations - Mehdi Jalalvand; Mohammad Reza Mokhtarzadeh; Sedigheh Toubaei (مدل‌سازی پیشرفته ریاضی)
In this paper, we propose a finite difference numerical method for the smooth solution of a system of linear Volterra integral equations. This method is a generalization of the finite difference method proposed in [11] and [12] for scalar linear Volterra integral equations. Error analysis of this method is presented via asymptotic expansion of the absolute error, and verification of accuracy is examined by two illustrative test problems.